Influência do porta-enxerto no vigor, floração e produção do pessegueiro em duas condições edafoclimáticas do Rio Grande do Sul - Comiotto, Andressa (2011)
This work was carried out with the objective to evaluate the vigour, flowering time, production and quality of peaches trees Maciel‟ and Chimarrita‟, on different rootstocks, in two edafoclimatic conditions in Rio Grande do Sul, Brasil. The experiment was conducted in two locations: at the Faculdade de Agronomia Eliseu Maciel, of Universidade Federal de Pelotas UFPel, in Pelotas (RS), Brasil, and at the Estação Experimental da Embrapa Uva e Vinho, in Bento Gonçalves (RS), Brasil, during the years 2008 and 2009. On both locations were evaluated the flowering time, grafting compatibility, trunk diameter, canopy volume, pruning weight, production, yield and yield efficiency in relation to the trunk diameter and canopy volume, fruit diameter and mass, fruit flesh firmness, soluble solid content (SS), titratable acidity (TA), SS/TA ratio, pH and external fruit color. The results showed that, regardless of where the orchard is placed, the rootstock interfere on vigour, and in phenological, productive and qualitative characteristics of peach trees Maciel‟ and Chimarrita‟. The cultivars Maciel‟ and Chimarrita‟, when grafted on Umezeiro‟ are less vigorous, in relation to that grafted on Capdeboscq‟, in any vigor comparison performed, due to a incompatibility with this rootstock. The Field Compatibility Constant (FCC), on both places evaluated, shows that the Umezeiro‟ rootstock has a little incompatibility with the cultivars Maciel and Chimarrita. The flowering time of the cultivars is influenced by the rootstocks; the beginning of the flowering and the full bloom can be delayed or forwarded by 5 days when cultivated in Pelotas, and until 11 days when cultivated in Bento Gonçalves. In Pelotas the cultivar Maciel had a higher cumulative yield when grafted on Tsukuba 1‟, and Chimarrita‟ when grafted on Aldrighi‟ and Capdeboscq‟. In Bento Gonçalves, Maciel‟ and Chimarrita‟ had the higher yield when grafted on Flordaguard‟. The combination between the cultivar Maciel and the rootstock Umezeiro produces peaches with higher SST/TA ratio, and the cultivar Chimarrita grafted on Umezeiro‟ produces peaches with higher SST, in Pelotas. Fruits of the cultivar Chimarrita‟, grafted on Capdeboscq‟ and Umezeiro‟ had a higher luminosity, and fruits of Chimarrita‟ grafted on Seleção Viamão‟ less luminosity and higher superficial color, in Pelotas. In Bento Gonçalves, Chimarrita‟ grafted on Umezeiro‟ produced peaches with the smaller SST/TA ratio. Chimarrita‟, grafted on Umezeiro‟, is less productive and produces fruits of smaller diameter, when cultivated in Bento Gonçalves.